STRATEGI PEMBINAAN OLEH PARA BHIKKHU DALAM MENINGKATKAN KEYAKINAN UMAT BUDDHA DI KABUPATEN LOMBOK UTARA - Kirta, Kirta; Dhammayanti, Wina; Sastrosupadi, Adji (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2021)
This study examines the increase in the belief of Buddhists in the North Lombok Regency after receiving guidance from monks. This study will describe the strategies applied by minks in increasing the belief of Buddhists in the North Lombok Regency for the period 2009-2020. This study used qualitative research methods. The data sources in this study used primary data, namely monks, and secondary data, namely from related books. The information in this study were three bhikkhus and three Buddhists who had been determined. The data collection instrument used in the interview guide that was proposed to the informant. Data analysis in this study used three stages, namely data condensation, data display, conclusion drawing/verification. The result of this study indicates that three is an increase in the belief of Buddhists after receiving direct guidance from the monks. The strategies applied in carrying out the coaching are carrying out a cultural approach, a forum for youth/women, and providing guidance to the community.